If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = (x + -2)(x + -2)(x + -2) Reorder the terms: 16 = (-2 + x)(x + -2)(x + -2) Reorder the terms: 16 = (-2 + x)(-2 + x)(x + -2) Reorder the terms: 16 = (-2 + x)(-2 + x)(-2 + x) Multiply (-2 + x) * (-2 + x) 16 = (-2(-2 + x) + x(-2 + x))(-2 + x) 16 = ((-2 * -2 + x * -2) + x(-2 + x))(-2 + x) 16 = ((4 + -2x) + x(-2 + x))(-2 + x) 16 = (4 + -2x + (-2 * x + x * x))(-2 + x) 16 = (4 + -2x + (-2x + x2))(-2 + x) Combine like terms: -2x + -2x = -4x 16 = (4 + -4x + x2)(-2 + x) Multiply (4 + -4x + x2) * (-2 + x) 16 = (4(-2 + x) + -4x * (-2 + x) + x2(-2 + x)) 16 = ((-2 * 4 + x * 4) + -4x * (-2 + x) + x2(-2 + x)) 16 = ((-8 + 4x) + -4x * (-2 + x) + x2(-2 + x)) 16 = (-8 + 4x + (-2 * -4x + x * -4x) + x2(-2 + x)) 16 = (-8 + 4x + (8x + -4x2) + x2(-2 + x)) 16 = (-8 + 4x + 8x + -4x2 + (-2 * x2 + x * x2)) 16 = (-8 + 4x + 8x + -4x2 + (-2x2 + x3)) Combine like terms: 4x + 8x = 12x 16 = (-8 + 12x + -4x2 + -2x2 + x3) Combine like terms: -4x2 + -2x2 = -6x2 16 = (-8 + 12x + -6x2 + x3) Solving 16 = -8 + 12x + -6x2 + x3 Solving for variable 'x'. Combine like terms: 16 + 8 = 24 24 + -12x + 6x2 + -1x3 = -8 + 12x + -6x2 + x3 + 8 + -12x + 6x2 + -1x3 Reorder the terms: 24 + -12x + 6x2 + -1x3 = -8 + 8 + 12x + -12x + -6x2 + 6x2 + x3 + -1x3 Combine like terms: -8 + 8 = 0 24 + -12x + 6x2 + -1x3 = 0 + 12x + -12x + -6x2 + 6x2 + x3 + -1x3 24 + -12x + 6x2 + -1x3 = 12x + -12x + -6x2 + 6x2 + x3 + -1x3 Combine like terms: 12x + -12x = 0 24 + -12x + 6x2 + -1x3 = 0 + -6x2 + 6x2 + x3 + -1x3 24 + -12x + 6x2 + -1x3 = -6x2 + 6x2 + x3 + -1x3 Combine like terms: -6x2 + 6x2 = 0 24 + -12x + 6x2 + -1x3 = 0 + x3 + -1x3 24 + -12x + 6x2 + -1x3 = x3 + -1x3 Combine like terms: x3 + -1x3 = 0 24 + -12x + 6x2 + -1x3 = 0 The solution to this equation could not be determined.
| 8x-25=3x+45 | | 1.33x-6x=2x+16 | | 64r^4-144r+81=0 | | 5/7x=-10 | | (48x^6-32x^4-40x^2)/(-8x^2) | | x^3-12x^2+12x-24=0 | | m-4.2=2.1m-0.9 | | 10x-7+2x-4=9x-3+2x | | 8/9x=-16 | | 2x+3=7x+8 | | x/3+x/8=11/24 | | logx-log(x+3)=-1 | | y=3x^3-27x^2+24x | | x-7=3(2x+1) | | 6/52x6/51 | | 2x+6=6x-1 | | y=3x^3-27x^2+24 | | 24/2=x/5 | | (X^2)+81=0 | | 5/7x-4/3=(3x+1)/2 | | 4(x-7)=11 | | 6/5x+2x=17 | | -3y-3y=-15 | | (4x+3)(4x+3)=225 | | n/4-8=-5 | | -3.5x=58.10 | | 35=n-(-16) | | 2y(x+4)=144y | | -(5x+3)-4=8+6x | | 8h+4=2h-20 | | jh=5 | | 4r^2=9/16 |